Tailoring the properties of electrolyzed Ni/mesostructured silica nanoparticles (MSN) via different Ni-loading methods for CO2 reforming of CH4 - Sidik, S. M. (Elsevier Ltd, 2016)
A series of Ni/mesostructured silica nanoparticles (NiM) catalysts from an electrolyzed Ni precursor were prepared by in-situ (NiM-IS), impregnation (NiM-IM), and physical mixing (NiM-PM) methods for CO2 reforming of CH4. N2 physisorption indicated that all preparation methods decreased the surface area and pore volume of the mesostructured silica nanoparticles (MSN) which may be attributed to the blockage of the pores by the deposition of NiO particles onto the MSN support. The XRD and H2-TPR analyses indicated that the in-situ method dispersed smaller Ni0 crystallites and exhibited a stronger metal-support interaction compared to the other methods. IR results indicated that the presence of an alkaline electrolyte during the introduction of Ni promoted sequential desilication-substitution of MSN, forming Si-O-Ni. CO2 adsorbed IR and ESR spectroscopies showed that NiM-IS possessed a higher basicity and more defect structures compared to NiM-IM and NiM-PM, owing to the abundant silanol groups and the formation of metal-deficient Ni2O3. At 800 °C, the CH4 and CO2 conversions occur in the order of NiM-IM (CH4 = 45.6 %, CO2 = 52.4%) <NiM-PM (CH4 = 60.5 %, CO2 = 83.9 %) <NiM-IS (CH4 = 94.3 %, CO2 = 91.7%). The amount of carbon deposited for NiM-IM, NiM-PM and NiM-IS was 2.97%, 2.35% and 0.84%, respectively. The promoting effect of the highest catalytic activity and lowest carbon deposition for NiM-IS was related to an intimate association between better dispersion and strongly interacted Ni, as well as high basicity and concentration of surface defects in the catalyst.